2015
DOI: 10.1039/c5cc02155c
|View full text |Cite
|
Sign up to set email alerts
|

DAST-promoted Beckmann rearrangement/intramolecular cyclization of acyclic ketoximes: access to 2-oxazolines, benzimidazoles and benzoxazoles

Abstract: The first example of DAST-promoted Beckmann rearrangement/intramolecular cyclization of acyclic ketoximes is described. This unique protocol represents a direct and effective pathway to 2-oxazolines, benzimidazoles and benzoxazoles in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…It should be mentioned that most recently Li and co-workers conducted the reaction of αcarbamoyl-α-oximyl cyclopropanes in the presence of DAST (diethylaminosulfur trifluride), and obtained the same compound 2a. 14 The efficiency of the synthesis of 5-iminooxazolines 2 was next examined by subjecting α, α-disubstituted β-oximyl amides 1h-l to the cyclization reaction under identical conditions. It was found that the reactions could furnish the corresponding 5-iminooxazolines 2hl in good to high yields (table 3, entries 1-5).…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that most recently Li and co-workers conducted the reaction of αcarbamoyl-α-oximyl cyclopropanes in the presence of DAST (diethylaminosulfur trifluride), and obtained the same compound 2a. 14 The efficiency of the synthesis of 5-iminooxazolines 2 was next examined by subjecting α, α-disubstituted β-oximyl amides 1h-l to the cyclization reaction under identical conditions. It was found that the reactions could furnish the corresponding 5-iminooxazolines 2hl in good to high yields (table 3, entries 1-5).…”
Section: Resultsmentioning
confidence: 99%
“…[44] DAST promoted Beckmann rearrangement and intramolecular cyclization of acyclic ketoximes has been presented as an alternative method to obtain 2-oxazolines (Scheme 24, Scheme 25), as well as benzimidazoles and benzoxazoles (Scheme 26). [45] Oxazolines bearing a cyclopropyl group at the R 3 position can constitute a spirocyclopropanated analogues of the most popular insecticide in the world -Imidacloprid. The yields of isolated compounds hovered from 60 % to 97 %.…”
Section: Heterocyclic Framework Synthesismentioning
confidence: 99%
“…The best isolated yield has been achieved in the reaction of substrate bearing fluorine atoms at the R 3 position and phenyl group at the R 2 position (Figure 5). [45] When o-arylamino-acetophenone-oximes 86, constituted the substrates, benzoimidazoles 87 were obtained as the major products and indazoles 88 as the minor products (Scheme 26). [45] The DAST mediated Beckmann fragmentation reaction was used in aryloyl and aliphatic acyl fluorides syntheses, which started from corresponding α-oximinoketones.…”
Section: Heterocyclic Framework Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…A rapid, stereoselective flow synthesis of 2-oxazolines from β-hydroxyamides was performed using Deoxo-Fluor (15OBC207) while a novel protocol involving diethylaminosulfur trifluoride (DAST)-promoted Beckmann rearrangement/intramolecular cyclization of ketoximes to give 114 was developed (15CC8637). A general synthesis of oxazolines 115 was also performed from β-acylamino ketones by I 2 -catalyzed CdO bond formation with TBHP in the presence of K 2 CO 3 (15OL3914).…”
Section: Oxazolinesmentioning
confidence: 99%